Membentuk Peserta Didik Memahami Pentingnya Kesempatan yang Sama dalam Memperoleh Pendidikan dan Pekerjaan - Armela Nababan; Eniwati Nduru; Lenny Lubis; Hisardo Sitorus (Jurnal Riset Rumpun Agama dan Filsafat, 2025)
Equality in education and employment is an important foundation for realizing social justice as mandated by Pancasila and the 1945 Constitution. Equality means that every individual has the same rights to access, treatment, and opportunities without discrimination based on gender, religion, ethnicity, social status, or physical condition. In education, equality is realized through equal access to learning facilities, an inclusive curriculum, and equal opportunities for all students to develop. Meanwhile, in the field of employment, equality includes fair opportunities in recruitment, promotion, training, and commensurate income. Education plays a strategic role in building awareness of equality by instilling the values ​​of empathy, tolerance, and social justice. A multicultural approach and inclusive education are key to shaping students who value diversity and reject discrimination. Although various policies have been implemented, such as the Smart Indonesia Card (KIP) and affirmative action programs for marginalized groups, challenges such as socio-economic inequality, discrimination, the digital divide, and weak policy implementation remain major obstacles. Therefore, comprehensive efforts are needed, encompassing policy reform, improving teacher quality, and implementing pluralism-based character education to create a just, inclusive, and equal Indonesian society.